D19 Longitudinal changes in functional connectivity of cortico-basal ganglia networks in manifest and premanifest huntington's disease. (13th September 2016) - Gargouri, Fatma; Messé, Arnaud; Perlbarg, Vincent; Valabregue, Romain; McColgan, Peter; Yahia-Cherif, Lydia; Fernandez-Vidal, Sara; Hamida, Ahmed Ben; Benali, Habib; Tabrizi, Sarah; Durr, Alexandra; Lehéricy, Stéphane
Abstract : Background: In Huntington's disease (HD), there is neuronal loss in distributed brain regions predominating in the basal ganglia but also present in the cortex. Functional imaging studies at rest have reported reduced long-range functional connectivity within motor areas as well as associative areas of the frontal and parietal lobes, the basal ganglia and the default mode network. Changes in functional connectivity over time in longitudinal studies in HD and preHD is less known although two studies did not find significant changes in connectivity over one- to three-year periods. Aims: We evaluated the changes in functional organisation within the sensorimotor, associative and limbic cortico-basal ganglia networks in preHD and HD patients compared with controls using resting-state fMRI (rs-fMRI) and graph theory over a two-year period. Methods: We acquired structural MRI and rs-fMRI in three visits one year apart, in 18 adult HD patients, 24 preHD and 18 gender- and age-matched healthy volunteers from the TRACK-HD study. We inferred topological changes in functional connectivity between 182 regions within cortico-basal ganglia networks using graph theory measures. Results: We found significant differences for global graph theory measures in HD but not in preHD. The average shortest path length (L) decreased, which indicated a change toward the random network topology. HD patients also demonstrated increases in degree k, reduced betweeness centrality bc and reduced clustering C. Changes predominated in the sensorimotor network for bc and C and were observed in all circuits for k. Hubs were reduced in preHD and no longer detectable in HD in the sensorimotor and associative networks. Conclusion: PreHD is characterised by progressive decrease in hub organisation, and these changes aggravate in HD patients with changes in local metrics.